The dual role of heme oxygenase in regulating apoptosis in the nervous system of Drosophila melanogaster - Abaquita, Terence Al L.; Damulewicz, Milena; Tylko, Grzegorz; Pyza, Elżbieta (Frontiers in Physiology, 2023)
Accumulating evidence from mammalian studies suggests the dual-faced character of heme oxygenase (HO) in oxidative stress-dependent neurodegeneration. The present study aimed to investigate both neuroprotective and neurotoxic effects of heme oxygenase after the ho gene chronic overexpression or silencing in neurons of Drosophila melanogaster. Our results showed early deaths and behavioral defects after pan-neuronal ho overexpression, while survival and climbing in a strain with pan-neuronal ho silencing were similar over time with its parental controls. We also found that HO can be pro-apoptotic or anti-apoptotic under different conditions. In young (7-day-old) flies, both the cell death activator gene (hid) expression and the initiator caspase Dronc activity increased in heads of flies when ho expression was changed. In addition, various expression levels of ho produced cell-specific degeneration. Dopaminergic (DA) neurons and retina photoreceptors are particularly vulnerable to changes in ho expression. In older (30-day-old) flies, we did not detect any further increase in hid expression or enhanced degeneration, however, we still observed high activity of the initiator caspase. In addition, we used curcumin to further show the involvement of neuronal HO in the regulation of apoptosis. Under normal conditions, curcumin induced both the expression of ho and hid, which was reversed after exposure to high-temperature stress and when supplemented in flies with ho silencing. These results indicate that neuronal HO regulates apoptosis and this process depends on ho expression level, age of flies, and cell type.